Cecropia pachystachya Trécul: a promising ingredient for skin-whitening cosmetics - Pedro Henrique Santos de Freitas; Jéssica Leiras Mota Conegundes; Monique de Rezende Evangelista; Maycon Alcântara de Almeida; Natália Prado da Silva; Guilherme Diniz Tavares; Fernanda Maria Pinto Vilela; Ana Paula do Nascimento Duque; Antônia Ribeiro; Elita Scio (Universidade de São Paulo, 2023)
Abstract Because it promotes the lightening of pigment spots, tyrosinase inhibition is one of the mechanisms of depigmenting cosmetic products. Considering the adverse effects produced by synthetic depigmenting actives, the search for new therapeutic options is desirable, and plant extracts are possible candidates for hyperpigmentation treatment. Glycolic extracts of Cecropia pachystachya Trécul are, therefore, the focus of this study. Its chemical characterization, antioxidant activity, tyrosinase inhibition, and cell viability were evaluated. Glycolic extracts were obtained by macerating the leaves of C. pachystachya in grain alcohol and glycerin or propylene glycol. Both had a similar chemical constitution, the glycerin being more efficient in concentrating phenolic compounds and flavonoids. Analyses by UHPLC-MS detected quinic acid, chlorogenic acid isomers, proanthocyanidin dimers type B and C, catechin/epicatechin, orientin/isoorientin, isoorientin 2"-O-xyloside, vitexin/isovitexin, and rutin. 5-O-caffeoylquinic acid was then quantified was then quantified, with predominance in the extract produced with propylene glycol. These extracts showed a high antioxidant capacity by the method of DPPH, β-carotene, and nitric oxide. As for depigmenting activity, both extracts were able to inhibit tyrosinase. Cell viability assay also revealed that the extracts could safely be used in concentrations of ≤ 125 µg/mL. Thus, this study demonstrated for the first time that the glycolic extracts of C. pachystachya have promising chemical and biological characteristics for the development of a multifunctional cosmetic with antioxidant and tyrosinase-inhibition activities.